Applicants’ Failure to Cooperate With State Authorities In The Process Of Restoration of Property Rights: Case-Law of ECtHR - Bruskina, Nika (Teisė, 2018)
[full article, abstract in Lithuanian; only abstract in English]The Article discusses the case-law of the European Court of Human Rights related to the applicants’ failure to cooperate with the State authorities in the process of restoration of property rights. In particular, the Article analyzes the role of the applicants’ failure to cooperate with the State authorities justifying the acts or inaction of the State authorities in the process of restoration of property rights under the Convention for the Protection of Human Rights and Fundamental Freedoms and Protocol No. 1 thereto.Seeking to establish whether the applicants’ wish to restore their property rights in a way that is not recognized under the domestic law is protected under the ECHR/Article No. 1 thereto, the Article begins with the analysis of margin of appreciation recognized to the contracting states under the ECHR in the field of restoration of property rights to the property taken from persons in the past (establishing the forms of restoration of property rights in the domestic law). Next, it is noted that the case-law of the ECtHR upholds the right of the State authorities to restore the property rights in a concrete way as established under the domestic law (by paying monetary compensation), when the persons within the time-limits provided for by the domestic law did not express their wish regarding the form in which the property rights could be restored or they expressed their wish regarding the form of restoration of the property rights, however, such a form is not established in the domestic law or it is impossible to restore the property rights in a form as indicated by the persons. The paper presents some conclusions concerning the justification of the length of the process of restoration of property rights under the ECHR/Protocol No. 1 thereto if the applicants themselves contributed to that length by their acts or inaction (e.g., when the applicant had the obligation to act in a concrete way under the domestic law and the State authorities could not finalize the process of restoration of property rights due to the lack of cooperation on the part of the applicant).
Keywords: none